La responsabilidad humana: El poema Pie para el Niño de Vallecas de Velázquez - Chen Sham, Jorge (2004)
The incorporation of an ekphrasis, a picture painted by Velásquez of the dwarf Lezcanillo, called "The boy of Vallecas" decodifies the sense of the poem by León Felipe, "Foot for the hoy of Vallecas by Velásquez", incorporating drarnatic elements which give intensity and dynamism to the pictorial representation. For that reason, thanks to the epigrafe the Iyric appeals to the necessity of a comrnitment in the face of injustice which is done by means of mediating the Cervantina dispute of the "barber's bowl" or of the "baciyelmo".